2015
DOI: 10.1007/978-3-319-28868-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Managing Intellectual Capital in Knowledge Economy

Abstract: Part 4: Components of Knowledge FlowInternational audienceStrategic Knowledge Management considers Intellectual Capital (IC) as roots of all organizations activities. The success of organizations strongly depends on the way they manage all facets of knowledge and skills. Artificial Intelligence brought some methods and techniques for handling intellectual assets of companies, expertise management, knowledge transfer and training. This paper presents an overview of experiences and research in applying artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Also, going by the work of Edvinsson and Bounfour [38], Nigeria would be said to have a lower value at the global development levels because of the fact that its intellectual capital has not create an impetus on the economic development. Hence, the development in Nigeria is questionable as confirmed by the work of Mercier-Laurent [41], and there may be no structural and economic development as affirmed by Pachura [42], and hence, the sustainability of the economy would be a major problem as attested by Makarov [43]. Consequently, one could say that the future of the nation is questionable and needs urgent attention if it must develop and survive in the recent global information economy and society and transformation.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, going by the work of Edvinsson and Bounfour [38], Nigeria would be said to have a lower value at the global development levels because of the fact that its intellectual capital has not create an impetus on the economic development. Hence, the development in Nigeria is questionable as confirmed by the work of Mercier-Laurent [41], and there may be no structural and economic development as affirmed by Pachura [42], and hence, the sustainability of the economy would be a major problem as attested by Makarov [43]. Consequently, one could say that the future of the nation is questionable and needs urgent attention if it must develop and survive in the recent global information economy and society and transformation.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Marcin [39] and Rusu-Tanasa [40] noted that intellectual capital is a major key factor of socioeconomic development of regions and countries. Mercier-Laurent [41] in trying to investigate intellectual capital management and the economy revealed that the focus on intellectual capital in any economy is due to the fact that it is the root of all organizations' activities which are directly contributors to the nation's economy or GDP. Pachura [42] noted that it aids structural and economic transformation in any nation.…”
Section: Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Wisdom thinking and knowledge can be defined as intellectual capital. This is an extraordinary positive value [30] for the city. Human and intellectual capital translates directly into the civilization level of the area [31].…”
Section: Government Perspectivementioning
confidence: 90%